Die Gemäldegalerie des Wiesbadener Museums - Weiler, Clemens; Museum Wiesbaden, Wiesbaden; Nassauischer Kunstverein, Wiesbaden (Hanau : Dr. Hans Peters Verlag, 1968)
Achenbach, Andreas ; Bartsius, Willem ; Baumeister, Willi ; Corinth, Lovis ; Dix, Otto ; Erler, Fritz ; Felixmüller, Conrad ; Hajek, Otto Herbert ; Jakob, Walter ; Kauffmann, Angelica ; Lehmbruck, Wilhelm ; Modersohn-Becker, Paula ; Nay, Ernst Wilhelm ; Primaticcio, Francesco ; Ritschl, Otto ; Stückgold, Stanislas ; Trübner, Wilhelm ; Wolff, Gustav Heinrich ; Zick, Januarius ; etc.
Duits
boek